Accounting for effects of growth rate when measuring ecological stability in response to pulse perturbations - Andrea Mentges; Adam Thomas Clark; Shane A. Blowes; Charlotte Kunze; Helmut Hillebrand; Jonathan M. Chase (Ecology and Evolution)
Abstract Ecological stability is a vital component of natural ecosystems that can inform effective conservation and ecosystem management. Furthermore, there is increasing interest in making comparisons of stability values across sites, systems and taxonomic groups, often using comparative synthetic approaches, such as meta‐analysis. However, these synthetic approaches often compare/contrast systems where measures of stability mean very different things to the taxa involved. Here, we present results from theoretical models and empirical data to illustrate how differences in growth rates among taxa influence four widely used metrics of ecological stability of species abundances responding to pulse perturbations: resilience, recovery, resistance and temporal stability. We refer to these classic growth‐rate‐dependent metrics as ‘realised’ stability. We show that realised resilience and realised temporal stability vary as a function of organisms' growth rates; realised recovery depends on the relation between growth rate and sampling duration; and realised resistance depends on the relation between growth rate and sampling interval. To account for these influences, we introduce metrics intended to be more independent of growth rates, which we refer to as ‘intrinsic’ stability. Intrinsic stability can be used to summarise the overall effects of a disturbance, separately from internal recovery processes – thereby allowing more general comparisons of disturbances across organisms and contexts. We argue that joint consideration of both realised and intrinsic stability is important for future comparative studies.